"Morbus hermeneuticus" - wyzwanie współczesnej humanistyki - Budzowska, Malgorzata (Collectanea Philologica, 2011)
The issue that is taken in the article concerns the problem of the essence of hermeneutics. Taking into consideration the Herbert Schnädelbach’s conception of “morbus hermeneuticus”, the author develops the reflection on the status of hermeneutics in philosophy. In the discussion about ideas of freedom of cognitive process the views of M. Polanyi, O. Marquard, R. Girard, G. Simmel, J. Baudrillard, M. Foucault, J. Derrida are presented. In addition, the author introduces the concepts of chaos theory and theory of contingency. Based on the indicated culture’s texts author tries to find a positive evaluation of hermeneutic method, which should be understood in a more extended sense and thus not seen as a state of disease (morbus hermeneuticus).